Theory of Mind (ToM) and language: stimulating metalinguistic skills in people with dementia - Rosell-Clari,Vicent (2016)
ABSTRACT Purpose The purpose of this paper was to assess the use of the Metalinguistic Skills Stimulation Program in Theory of Mind (ToM) in people with dementia. Methods An experimental research design was developed. Forty-two subjects, 28 women and 14 men, aged 61 to 87 participated in the study. The three following groups were created: Experimental Group and Control Group - both composed of people with dementia, and Normal Group - consisting of people without dementia or any medical and psychological disorders that keep them from living a normal life. All subjects in the sample were evaluated using the MMSE30 Test and the MetAphAs Test. The stimulation program was used with the Experimental Group in 40-minute sessions held twice a week for five months. After the program, a second evaluation or retest was performed. The data obtained were compared statistically and qualitatively, individually and between the different groups. Results A clear effect of the treatment was observed: most of the patients improved their average scores in the performance of various tasks and on the MetAphAs Test. Significant differences were observed when comparing the Experimental Group with the Control Group. Conclusions The evolution of each patient presents a multifactorial etiology, and it was influenced by different variables related to the patients and their psychosocial environment. The data encourage the development of further research with larger samples in order to achieve more conclusive results.